DEVELOPMENT OF FOOD COMPOSITIONS OF PRODUCTS FOR PEOPLE UNDER CONDITIONS OF CONSTANT STRESS (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article addresses the physiological and dietary challenges posed by chronic stress, a pervasive issue in contemporary society. Chronic stress significantly impacts the human central nervous system, leading to behavioral changes, social withdrawal, and health problems. The authors emphasize the need for tailored dietary interventions to bolster the body's resilience and functional capacity in high-stress environments.The study introduces innovative approaches to formulating functional food products enriched with essential nutrients such as zinc, magnesium, iron, and copper, which play critical roles in stress adaptation. It explores the benefits of incorporating plant-based dietary supplements, including pumpkin seed fiber and wheat germ, which provide natural stress-protective agents. Analytical research conducted by specialists at the "Zhytomyr Bioproduct" NGO demonstrates the positive effects of these compositions in meeting daily nutritional requirements.A key focus of the paper is the development of a specialized meat-and-offal pâté designed to address the nutritional needs of individuals under chronic stress. The product's formula integrates animal proteins, plant-derived fibers, and antioxidant-rich vitamins to enhance its stress-relief properties. The inclusion of local natural resources underscores the importance of region-specific dietary solutions.This comprehensive research provides a scientific basis for creating functional foods aimed at mitigating the adverse effects of stress while supporting overall health. It underscores the necessity of interdisciplinary collaboration in developing dietary strategies to combat chronic stress effectively.
Keywords: stress; adaptation mechanisms; functional food; nutrient modeling; chronic stress management